Seroprevalence of Japanese encephalitis virus using competitive enzyme linked immunosorbent assay (C-ELISA) in pigs in East Sumba, Indonesia - Detha, Annytha; Wuri, Diana A.; Santhia, Ketut (Journal of Advanced Veterinary and Animal Research, 2015)
Japanese Encephalitis (JE), a vector-borne zoonotic viral disease, is mostly prevalent in Asian countries. The objective of this study was to investigate the occurence of JE virus (JEV) among pigs in East Sumba, Indonesia. Blood samples (n=52) were randomly collected from 52 apparantly healthy pigs where pig population was high in East Sumba. The samples were subjected for seroprevalence study for the presence of antibodies against JEV using competitive enzyme linked immunosorbent assay (C- ELISA). Results showed that 53% (n=28/52) blood samples from the pigs contained antibodies against JEV. This finding is suggestive that the JEV is circulating among pig population in East Sumba, Indonesia. The data may help in designing control strategies of the JEV in the East Sumba, Indonesia. http://dx.doi.org/10.5455/javar.2015.b112